Accounting Practices of Travelers’ Income based on Local Wisdom Values: An Islamic Ethnomethodology Study - Thalib, Mohamad Anwar; Roni Mohamad (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
Abstract: Introduction/Main Objectives: This study aims to explore the income accounting practices of travelers from Gorontalo to Mecca using bicycles, focusing on the integration of local wisdom values. It seeks to understand how these travelers manage their income in alignment with Islamic teachings. Background Problems: Despite extensive research on accounting practices, there is limited exploration of how travelers apply local wisdom in income management during religious journeys. This study addresses this gap by investigating how travelers generate and document their income. Novelty: This study introduces an Islamic ethnomethodological approach to examining income accounting practices, highlighting the role of gratitude and cultural values in financial management, an aspect not widely explored in previous research. Research Methods: The study adopts a qualitative research method using structured interviews. Data analysis follows five stages: charity, knowledge, faith, revelation information, and courtesy. Findings/Results: The findings reveal various income accounting practices, including revenue sources from selling t-shirts, recording income based on memory, and price differentiation between Indonesia and Singapore to optimize earnings. These practices reflect a deep sense of gratitude toward the Creator. In Gorontalo’s Islamic culture, gratitude is expressed through the proverb "Diila o’onto, bo wolu-woluwo," meaning "what is unseen exists," which signifies the balance between material and spiritual pursuits. Conclusion: The study concludes that travelers' income accounting practices are deeply rooted in Islamic teachings and local wisdom, emphasizing gratitude as a fundamental value in financial management. These insights contribute to the broader understanding of accounting practices within cultural and religious contexts. Keywords: Islamic accounting, income management, local wisdom, ethnomethodology, traveler finance Abstrak:Tujuan/Pendahuluan: Penelitian ini bertujuan untuk mengeksplorasi praktik akuntansi pendapatan para traveler dari Gorontalo ke Mekah dengan sepeda, yang mengintegrasikan nilai-nilai kearifan lokal dalam pengelolaan pendapatan mereka. Masalah Latar Belakang: Meskipun terdapat banyak penelitian tentang praktik akuntansi, masih sedikit kajian yang membahas bagaimana para traveler menerapkan kearifan lokal dalam manajemen pendapatan selama perjalanan religius. Studi ini mengisi kesenjangan tersebut dengan meneliti bagaimana mereka memperoleh dan mencatat pendapatan. Kebaruan: Penelitian ini memperkenalkan pendekatan etnometodologi Islam dalam mengkaji praktik akuntansi pendapatan, menyoroti peran rasa syukur dan nilai budaya dalam pengelolaan keuangan, aspek yang belum banyak dibahas dalam penelitian sebelumnya. Metode Penelitian: Penelitian ini menggunakan metode kualitatif dengan teknik wawancara terstruktur. Analisis data dilakukan dalam lima tahapan, yaitu amal, ilmu, iman, informasi wahyu, dan ihsan. Hasil Temuan: Temuan menunjukkan bahwa terdapat berbagai praktik akuntansi pendapatan, seperti sumber pendapatan dari penjualan kaos, pencatatan pendapatan berbasis ingatan, serta perbedaan harga jual antara Indonesia dan Singapura untuk mengoptimalkan pendapatan. Praktik ini mencerminkan rasa syukur yang mendalam kepada Sang Pencipta. Dalam budaya Islam Gorontalo, rasa syukur ini diwujudkan dalam ungkapan "Diila o’onto, bo wolu-woluwo," yang berarti "yang tidak terlihat itu ada," mengajarkan keseimbangan antara aspek material dan spiritual. Kesimpulan: Studi ini menyimpulkan bahwa praktik akuntansi pendapatan para traveler berakar kuat dalam ajaran Islam dan nilai-nilai kearifan lokal, dengan menekankan rasa syukur sebagai prinsip utama dalam praktik akuntansi pendapatan. Temuan ini memberikan kontribusi pada pemahaman yang lebih luas tentang praktik akuntansi dalam konteks budaya dan agama. Kata kunci: Akuntansi Islam, manajemen pendapatan, kearifan lokal, etnometodologi, keuangan traveler